Autoimmune markers in children with chronic pancreatitis - Oracz, Grzegorz; Cukrowska, Bożena; Kierkuś, Jarosław; Ryżko, Józef (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : In the last decade we can observe a gradual increase in the incidence of autoimmune diseases. The aetiology of chronic pancreatitis (CP) in children is varied and includes gene mutations, anatomic anomalies and others. The reported paediatric experience with chronic CP is scarce and little is known about the role of autoimmune pancreatitis (AIP). Aim: To assess the frequency of autoimmune markers in children with CP. Material and methods: One hundred and twenty-nine children hospitalised between 2005 and 2012 at the Department of Gastroenterology, The Children’s Memorial Health Institute, were examined for the presence of AIP; the level of IgG4 was determined, and tests for anti-tissue antibodies (ANA, ASMA, AMA, ANCA, AHA) were conducted. Clinical data were recorded and analysed. Results: Anti-tissue antibodies were detected in 75/129 children (58%), and 24/68 patients (35.3%) showed an increased IgG4 level. Based on the International Association of Pancreatology criteria, a suspicion of AIP was raised in 6 patients (4.6%). We found gene mutations predisposing to CP in 32/75 (42.6%) patients with autoimmune markers. In 16/75 children (21.3%), anatomic anomalies were found. There was no difference in the severity of the disease and clinical course between children with evidence of autoimmune process and patients without autoimmune markers (p = NS). Conclusions: In children with CP, similarly to adults, there is a high frequency of biochemical markers of autoimmunity. It is worth remembering that AIP can occur in children.